EVALUASI EVALUASI FASILITAS PRASARANA STASIUN PURWOSARI BERDASARKAN PERSEPSI PENGGUNA: EVALUATION OF PURWOSARI STATION INFRASTRUCTURE FACILITIES BASED ON USER PERCEPTION - Edelbertus Kurnialdi Waru; Handayani, Ani Tjitra; Veronica Diana Anis Anggorowati (Retii, 2024)
Trains are one of the alternatives in the development of transportation that requires efficiency of transportation capacity, time, and durability as well as comfort, both facilities and infrastructure. Research objectives: a) To determine user perceptions of Purwosari Station infrastructure facilities. b) To determine user satisfaction with Purwosari Station infrastructure facilities. c) To determine facilities that require improvement regarding Purwosari Station infrastructure facilities. The research method used in the study is IPA (important performance analysis). Data collection techniques are carried out manually in the field by distributing questionnaires to Purwosari Station users. Based on the results of the analysis of the level of suitability and quadrant analysis, it is concluded that the reliability and regularity variables are achievements that need to be maintained by the station because they have the highest percentage, namely 89.03% and for the convenience variable it has a percentage of 88.22%. For the safety variable, it has the highest level of satisfaction, namely with a score of 416. There are no facilities that require repair, because based on the results of the quadrant analysis, there are no items in quadrant I. Keywords: Train, User Satisfaction, Purwosari Station, Questionnaire.